"The Homecoming” : A Novel and “Time, Self and Metaphor in Illness Stories” : An Exegesis - Stevens, Rosemary Winifred (Curtin University, 2012)
This thesis comprises a creative work in the form of a novel, and an academic exegesis. Together they address the question of how narrative representations of time can be used to reconfigure a selfhood undermined by temporal disruption due to illness. In view of the fact that narrative is traditionally defined by temporal succession and causal relationship, it becomes problematic when both are distorted. This thesis examines temporal perception in illness, its effects on the self and the role narrative plays in reconfiguring the self. In short, it addresses the question; how might the ill protagonist tell their story when they have, quite literally, lost the plot ?In my novel, The Homecoming, a breast cancer diagnosis acts as a catalyst for change for Helen, a middle-aged woman, whose mother, Vera, has recently suffered a stroke. The reconciliation of mother and daughter through their illness crises forms the central theme.The exegesis analyses autobiographical and fictional illness stories for relationships between illness, self and temporal representation, with particular emphasis on the form of the novel. My main focus is on metaphor and its ability to effect or negate self-change in the sufferer. I argue that, on the one hand, when metaphor is striking and original it serves as a temporal bridge to reunite the emergent self with aspects disassociated through illness. On the other hand, dead or clichéd tropes undermine efforts to integrate the present health crisis with one’s former and therefore future self. My conclusion is that metaphor acts as an important transformational medium, not only for the illness protagonist (whether memorial or fictional), but also for the reader.